Ndlovu-Gatsheni, Sabelo J. (ed), Mugabeism? History, Politics, and Power in Zimbabwe. New York: Palgrave Macmillan, 2015, 319pp. (The Strategic Review for Southern Africa, 2020)
This is an 'all in one' kind of book about the history, politics, and economy of Zimbabwe from the liberation struggle on. The book is about Robert Mugabe and his Mugabeism, or what Mugabe 'says' he is and what he Strategic Review for Southern Africa, Vol 38, No 2 Book Reviews 174 'exactly is'. It responds to the lack of biographies on Mugabe who is the oldest and the longest serving post-independence African statesman, the man whose life has been dominated by secrecy, rumours and gossip. The book consists of several essays written by scholars from different disciplines, trying to make sense of Mugabe by exploring the various, contested meanings of the Mugabe phenomenon, his thinking, his feeling and his modus operandi. With convincing arguments, the book shows how the life of Mugabe is intrinsically linked to the history of Zimbabwe and ZANU-PF. The book reveals the great secret of how Mugabe has survived internal and external challenges and pressures.